Optimization of the electrochemical performance of a composite polymer electrolyte based on pva-k2 co3-sio2 composite - Abdulkadir, B.A. (MDPI AG, 2021)
Composite polymer electrolyte (CPE) based on polyvinyl alcohol (PVA) polymer, potassium carbonate (K2 CO3 ) salt, and silica (SiO2 ) filler was investigated and optimized in this study for improved ionic conductivity and potential window for use in electrochemical devices. Various quan-tities of SiO2 in wt. were incorporated into PVA-K2 CO3 complex to prepare the CPEs. To study the effect of SiO2 on PVA-K2 CO3 composites, the developed electrolytes were characterized for their chemical structure (FTIR), morphology (FESEM), thermal stabilities (TGA), glass transition temperature (differential scanning calorimetry (DSC)), ionic conductivity using electrochemical impedance spectroscopy (EIS), and potential window using linear sweep voltammetry (LSV). Physicochemical characterization results based on thermal and structural analysis indicated that the addition of SiO2 enhanced the amorphous region of the PVA-K2 CO3 composites which enhanced the dissociation of the K2 CO3 salt into K+ and CO32â and thus resulting in an increase of the ionic conduction of the electrolyte. An optimum ionic conductivity of 3.25 Ã 10â4 and 7.86 Ã 10â3 mScmâ1 at ambient temperature and at 373.15 K, respectively, at a potential window of 3.35 V was observed at a composition of 15 wt. SiO2 . From FESEM micrographs, the white granules and aggregate seen on the surface of the samples confirm that SiO2 particles have been successfully dispersed into the PVA-K2 CO3 matrix. The observed ionic conductivity increased linearly with increase in temperature confirming the electrolyte as temperature-dependent. Based on the observed performance, it can be concluded that the CPEs based on PVA-K2 CO3-SiO2 composites could serve as promising candidate for portable and flexible next generation energy storage devices. Â© 2020 by the authors. Licensee MDPI, Basel, Switzerland.